Influential Article Review - Device Diversity and Product Performance: An Analysis of The Mobile Technology Industry - Buchanan, Sergio; Wolfe, Shawna; Newton, Curtis (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: The platform economy is becoming an important engine for industrial innovation and economic growth. However, empirical research on how platform governance affects product performance through network externalities remains limited. Leveraging the perspective of platform ecosystems, this paper intends to empirically investigate the impact of platform governance on the product performance of complementors in the mobile application industry, based on firstly released apps on Apple’s App Store and Google Play. Our study shows that complementors of free mobile applications on the weakly regulated platform, Google Play, perform much better than those on the strictly regulated platform, Apple’s App Store, due to the larger size of the installed base. However, complementors on the strictly regulated platform, Apple’s App Store, can take advantage of highly valued end-users on the demand side and higher degrees of product differentiation on the supply side to enhance their product performance. This is likely due to higher entry barriers for complementors, and better user communities for end-users. We suggest that higher competition efficiency and performance levels are linked to the platforms associated with strict governance. The platform economy is becoming an important engine for industrial innovation and economic growth. However, empirical research on how platform governance affects product performance through network externalities remains limited. Leveraging the perspective of platform ecosystems, this paper intends to empirically investigate the impact of platform governance on the product performance of complementors in the mobile application industry, based on firstly released apps on Apple’s App Store and Google Play. Our study shows that complementors of free mobile applications on the weakly regulated platform, Google Play, perform much better than those on the strictly regulated platform, Apple’s App Store, due to the larger size of the installed base. However, complementors on the strictly regulated platform, Apple’s App Store, can take advantage of highly valued end-users on the demand side and higher degrees of product differentiation on the supply side to enhance their product performance. This is likely due to higher entry barriers for complementors, and better user communities for end-users. We suggest that higher competition efficiency and performance levels are linked to the platforms associated with strict governance. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.